Implementation of a sanction scanner to the internal IT audit system - Kedrovskyi, Serhii (2024)
This thesis focuses on the implementation of the sanctions scanner at KPMG.  The aim of the project is to create the company’s own application for finding undesirable users in lists. Before this project, KPMG had not used any other applications to solve this problem.  This application will allow to analyze users, a service that had not previously been provided by the company. The main task is to create an initial working application to be implemented in the company's local system.  This paper consists of five main parts. In the first part, the reader is familiarized with how this project came about and its objectives. The second part will analyze the market in this area. The third part will detail the step-by-step development of the application. This is followed by the fourth part, which will describe the implementation of the application in the internal system. The final part will describe how the application works in the company and its further development to improve its quality or expand its functionality.